Why Jane Austen? - Brownstein, Rachel M. (Columbia University Press, 2011)
Rachel M. Brownstein considers Jane Austen as heroine, moralist, satirist, romantic, woman, and author, along with the changing notions of these categories over time and texts. She finds echoes of many of Austen's insights and techniques in contemporary Jane-o-mania, a commercially driven, erotically charged popular vogue that aims to preserve and liberate, correct and collaborate with old Jane.